Immune cell subsets in interface cutaneous immune‐related adverse events associated with anti‐PD‐1 therapy resemble acute graft versus host disease more than lichen planus. (16th May 2022) - Almodovar Cruz, Guillermo E.; Kaunitz, Genevieve; Stein, Julie E.; Sander, Inbal; Hollmann, Travis; Cottrell, Tricia R.; Taube, Janis M.; Sunshine, Joel C.
Abstract: Background: Checkpoint immunotherapy is frequently associated with cutaneous immune‐related adverse events (cirAEs), and among those, the most common subtype shows interface reaction patterns that have been likened to lichen planus (LP); however, cutaneous acute graft versus host disease (aGVHD) may be a closer histopathologic comparator. We used quantitative pathology to compare the immunologic composition of anti‐PD‐1‐associated interface reactions to LP and aGVHD to assess for similarities and differences between these cutaneous eruptions. Methods: Immunohistochemistry for CD4, CD8, CD68, PD‐1, and PD‐L1 was performed on formalin‐fixed paraffin‐embedded tissue from patients with anti‐PD‐1 interface cirAEs ( n  = 4), LP ( n  = 9), or aGVHD ( n  = 5). Densities of immune cell subsets expressing each marker were quantified using the HALO image analysis immune cell module. Plasma cell and eosinophil density were quantified on routine H&E slides. Results: Specimens from patients with anti‐PD‐1 interface cirAEs showed equivalent total cell densities and immune cell composition to those with aGVHD. Patients with LP showed higher total immune cell infiltration, higher absolute T‐cell densities, increased CD8 proportion, and reduced histiocytic component. The cases with the highest plasma cell counts were all anti‐PD‐1 interface cirAEs and aGVHD. Conclusion: The composition of immune cell subsets in anti‐PD‐1 interface cirAEs more closely resembles the immune response seen in aGVHD than LP within our cohort. This warrants a closer look via advanced analytics and may have implications for shared pathogenesis and potential treatment options.